Arabic in Contact - Manfredi, Stefano; Tosco, Mauro (John Benjamins Publishing Company, 2018)
The present volume provides an overview of current trends in the study of language contact involving Arabic. By drawing on the social factors that have converged to create different contact situations, it explores both contact-induced change in Arabic and language change through contact with Arabic. The volume brings together leading scholars who address a variety of topics related to contact-induced change, the emergence of contact languages, codeswitching, as well as language ideologies in contact situations. It offers insights from different theoretical approaches in connection with research fields such as descriptive and historical linguistics, sociolinguistics, ethnolinguistics, and language acquisition. It provides the general linguistic public with an updated, cutting edge overview and appreciation of themes and problems in Arabic linguistics and sociolinguists alike. As of January 2023, this e-book is freely available, thanks to the support of libraries working with Knowledge Unlatched.